Presidential Decree-Law No. 58 of the year 2014 Concerning the cancellation of Decree-Law No. 102 of the year 2012 Amending Some Provisions of the General Sales Tax Law No. 11 of the year 1991 And the Amendment of Certain Provisions of the General Sales Tax Law = قرار رئيس جمهورية مصر العربية بالقانون رقم 58 لسنة 2014 بإلغاء القرار بالقانون رقم 102 لسنة 2012 المعدل لبعض أحكام قانون الضريبة العامة على المبيعات الصادر بالقانون رقم 11 لسنة 1991 وتعديل بعض أحكام قانون الضريبة العامة على المبيعات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.